The importance of clinical trial protocols - de Moraes Silva, Melissa Andreia (2024)
The International Committee of Medical Journal Editors (ICMJE) and the World Health Organization (WHO) define a clinical trial as any research that prospectively assigns participants or groups of human subjects to one or more interventions (medicines, procedures, devices, behavioral treatments, dietary supplements and diets, for example). These trials aim to evaluate the effects of interventions on human health. Prospective clinical research is essential for discovering new knowledge, improving the scientific base, solving challenges, and improving clinical practices. The basic principles for a successful researcher include interest, availability, persistence, and honesty. However, it is essential that, first of all, one has complete and detailed knowledge of scientific writing and preparation of the research protocol.